A Compact Low-Permittivity Dual-Layer EBG Structure for Mutual Coupling Reduction - A. Azarbar; J. Ghalibafan (International Journal of Antennas and Propagation)
Electromagnetic bandgap (EBG) structures can help in the reduction of mutual coupling by their capabilities of suppressing surface wave's propagation in a specific frequency range. In this work, a dual-layer EBG structure, which had a lower resonant frequency than the single-layer one, is proposed in order to reduce the mutual coupling between 𝐸-plane coupled microstrip antenna array. As this EBG structure significantly made the series capacitance between neighbor cells larger, a drastic reduction of the unit cell size was achieved. The simulated and experimental results show that the proposed structure has a significant 19 dB mutual coupling reduction.